Program Pelatihan Manajemen Sumber Daya Manusia dalam Usaha Agribisnis di Desa Ganjar Asri - Subandi; Yunita Widia Putri; Ghati Firmansyah (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2022)
Abstract: This work program aims to increase the capacity of agribusiness actors in Ganjar Asri Village in managing human resources (HR) effectively and systematically. Based on the results of the initial assessment, the majority of agribusiness actors do not understand the basics of HR management. Activities were carried out using the Asset-Based Community Development (ABCD) and Community-Based Research (CBR) approaches to explore local strengths and empower the community as equal partners. The methods used included asset mapping, focus group discussions, participatory training, and field assistance. The results showed an increase in participants' understanding by 60%, as well as the application of new managerial practices in their businesses. This program is expected to be replicated and sustainable to strengthen village agribusiness institutions. Keywords: human resource management, agribusiness